2020
DOI: 10.1186/s40494-020-0358-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and characterization of materials used in heritage theatrical figurines

Abstract: The precious collections of the Qing Dynasty paper-made theatrical figurines known as Shage xiren (纱阁戏人) represent a unique type of Chinese traditional folk art. The name, "Shage xiren" can be explained as the theatrical figurines that display in gauze curtains covered showcases. There were originally 36 showcases of Shage xiren of which 34 are preserved with 28 showcases exhibited at Qingxu Taoist Temple of Pingyao and the other damaged 6 are kept in the storeroom. It is rare that ancient paper-made figurines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Although studies on the sculptures have been conducted over the years [1,2], only a few technical studies have been reported for the conservation of other sculptures and there is no previous technical investigation of the materials and techniques used in making the sculptures in Jingyin Temple. Considering all these modern methods, the combination of Environmental Scanning Electron Microscopy with Energy Dispersive X-ray analysis (ESEM/EDX), Raman spectroscopy and Polarized light microscopy (PLM) has proved to be a powerful methodology to identify the pigments [6][7][8]. Application of X-ray diffraction (XRD) is beneficial for accurately identifying crystalline structures in muds [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although studies on the sculptures have been conducted over the years [1,2], only a few technical studies have been reported for the conservation of other sculptures and there is no previous technical investigation of the materials and techniques used in making the sculptures in Jingyin Temple. Considering all these modern methods, the combination of Environmental Scanning Electron Microscopy with Energy Dispersive X-ray analysis (ESEM/EDX), Raman spectroscopy and Polarized light microscopy (PLM) has proved to be a powerful methodology to identify the pigments [6][7][8]. Application of X-ray diffraction (XRD) is beneficial for accurately identifying crystalline structures in muds [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patterns in traditional Chinese folk costumes come from life and are influenced by the background of the times, people's beliefs and local customs [6]. The common pattern images in Yunjian can be broadly divided into plant, animal, character, artifact and text categories.…”
Section: Pattern Themementioning
confidence: 99%
“…Certain analytical methods have already been proven to be effective in the scientific analysis of the various structures of ancient polychromic artworks, including surface or cross-section observation using optical microscopy [ 3 ], digital microscopy [ 4 ] and scanning electron microscopy (SEM) [ 5 ]; X-ray diffraction (XRD) [ 6 ] and SEM [ 7 ] are particularly beneficial for accurately identifying the crystalline structures and microstructure of the clay ground layer while a combination of Herzberg stain and optical microscopy is commonly used to identify the fibre sources in ground clay layers [ 8 ]; particle induced X-ray emission spectroscopy (PIXE) [ 9 ], X-ray fluorescence (XRF) [ 10 ] or energy dispersive spectroscopy (EDS) [ 11 ] have also been used to analyse the elements of the relevant mineral pigments, and a combination of Raman spectroscopy (RS) [ 12 , 13 ], Fourier transform infrared spectroscopy (FT-IR) [ 12 , 13 ] and XRD [ 7 ] have also been found to be beneficial for accurately identifying pigments.…”
Section: Introductionmentioning
confidence: 99%